New zones of coexistence in the cultural field the popular literary magazines in Turkey - İmamoğlu, Efe (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Kültürel alanda yeni 'Bir Anda Var Olma' bölgeleri: Türkiye'de popüler edebiyat dergileri